THE DESIGN OF A SAVING AND LOAN APLLICATION USING A WEB-BASED PROGRAMMING LANGUAGE - Putra, Eka; Putra, Randi Rian (Proceeding International Conference of Science Technology and Social Humanities, 2022)
At the Kelambir Lima Village Head Office, the village government data processing process is currently not optimal because the village government data processing still uses Microsoft Office. Data processing like this can lead to data loss or insecure data in storage. Therefore, the research will create a data processing system with sufficient computerization. So that the report that will be needed can be processed appropriately by the office of the head of the village of Kelambir Lima. From the problems that have been obtained so that a solution is obtained from its handling by implementing a web-based village government application.